Physiotherapeutic techniques for the management of patellar tendinopathy (Research, Society and Development, 2021)
Patellar tendinopathy is a condition related to the overload of the knee extensor apparatus. This lesion affects the patella, causing pain on palpation and functional deficit. The most affected segment is the deep and posterior portion of the patellar tendon, adjacent to the inferior pole of the patella. It is also known by the name of jumper's knee or “jumper's knee”, as it is common in athletes who practice jumping, and can be divided into 4 degrees of pain. Physiotherapy promotes improvement in pain, muscle balance, gain in range of motion, having a fundamental role in the recovery of functionality through therapeutic methods, being performed in conjunction with the use of analgesics and support devices. The most used treatment methods are kinesiotherapy, electrotherapy, stretching, patellar bandage, in addition to cryotherapy. The objective of this work is to discuss the physiotherapeutic techniques for the management of patellar tendinopathy. Methodology: the article is a narrative literature review. For the realization of this article, filtering was performed on Google Scholar, Scielo and PubMed platforms, the selected articles were all related to the proposed topic from the etiology of tendinopathy, through the techniques used in physical therapy treatment. Conclusion: The techniques that showed the greatest benefits in the acute phase were kinesiotherapy, mainly by performing eccentric exercises as well as stretching techniques that help in the patient's flexibility and improve motor function, this technique, in addition to these benefits, can also act in prevention of the development of tendinopathy. In the chronic phases of the disease, the technique that showed an improvement in the treatment was electrotherapy, as it helps in healing and increases the tendon's tensile strength, for pain control the technique that most stood out was cryotherapy, as it helps in the relief of localized pain even though there is still no consensus on its adequate application.